Analysis of the Dose-Response Relationship Between the International Normalized Ratio and Hepatic Encephalopathy in Patients With Liver Cirrhosis Using Restricted Cubic Spline Functions - Tan, Juntao; He, Yuxin; Li, Zhanbiao; Zhang, Qinghua; Yang, Yanzhi; Xu, Qian; Xu, Xiaomei (Frontiers in Public Health, 2022)
Background: The International Normalized Ratio(INR) is significantly associated with Hepatic Encephalopathy(HE) in patients with liver cirrhosis. However, the dose-response relationship between continuous INR changes and HE risk has not been clearly defined. Thus, our goal was to explore the continuous relationship between HE and INR among patients hospitalized with liver cirrhosis and to evaluate the role of the INR as a risk factor for HE in these patients. Methods: A total of 6266 people were extracted from the Big Data Platform of the Medical Data Research Institute of Chongqing Medical University. In this study, unconditional logistic regression and restricted cubic spline (RCS) model were used to analyze the dose-response association of INR with HE. Alcoholic liver disease, smoking status, and drinking status were classified for subgroup analysis. Results:The prevalence of HE in the study population was 8.36%. The median INR was 1.4. After adjusting for alcoholic liver disease, age, smoking status, drinking status, total bilirubin, neutrophil percentage, total hemoglobin, aspartate aminotransferase, serum sodium, albumin, lymphocyte percentage, serum creatinine, red blood cell, and white blood cell, multivariate logistic regression analysis revealed that INR ≥ 1.5 (OR=2.606, 95%CI: 2.072-3.278) was significantly related to HE risk. The RCS model showed a nonlinear relationship between the INR and HE (nonlinear test, χ2 = 30.940, P < 0.001), and an increased INR was an independent and adjusted dose-dependent risk factor for HE among patients with liver cirrhosis. Conclusion: This finding could guide clinicians to develop individualized counseling programs and treatments for patients with HE based on the INR risk stratification.